Nitrogen Mineralization and Different Methods of Ammonium Determination of Some Paddy Soils in the North, Central, and Northeast Regions of Thailand - Khaokaew, Wasana; Attanandana, Tasnee; Chanchareonsook, Jongrak; Sripichitt, Prapa; Yost, Russell (Agriculture and Natural Resources, 2007)
High yields of rice are needed for farmer profitability and to provide this most important staple food and cash export crop of the country. Nitrogen fertilizer management is one of the key factors for high yielding of rice. Good management will reduce the contamination of the environment. Nitrogen mineralization or ammonium release after submergence is a useful index of nitrogen supplying capacity of the soils. The data is useful for effective fertilizer application. The study on ammonium release of 18 soil series which are the representative rice soils in the North, Central and Northeast regions of Thailand was performed. The results showed that ammonium release from 18 soils increased with time of submergence and the content reached the steady state at 4 weeks of submergence. The amount released of the soils followed the equation : Y = A-Be-ct except in the four soils. The higher ammonification percentage was found in soils lower in total N and clay content. Mehlich 1 and 0.25 M H2SO4 were the promising extracting solutions for assessing the initial amount of ammonium in the dry soils.